Maximizing bandwidth in CCII for wireless optical applications - Alves, L. N.
This paper discusses bandwidth problems associated with the usage of second-generation current conveyors in wireless optical systems, and presents a new current amplifier with wide bandwidth and large input dynamic range, developed for Fast Ethernet wireless applications This current amplifier is used to interconnect low cost photo-detectors (with large intrinsic capacitance) with transimpedance amplifiers, overcoming typical bandwidth limitations imposed by the input transducers. This current adaptation concept has proved to be adequate for increasing both bandwidth and dynamic range of traditional optical interfaces. The proposed current amplifier architecture is based on a CCII with reduced input impedance and achieves, for a lOpF input photo detector, a maximum gain of 18dB with a 130MHz bandwidth, with a noise floor of 9.2pA/√Hz,. The expected input dynamic range is larger than 65dB. © 2001 IEEE.